2021
DOI: 10.3390/ijms22042013
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Chromatin Structure and Transcription Changes in Plant Stress Response

Abstract: Sessile plants are exposed throughout their existence to environmental abiotic and biotic stress factors, such as cold, heat, salinity, drought, dehydration, submergence, waterlogging, and pathogen infection. Chromatin organization affects genome stability, and its dynamics are crucial in plant stress responses. Chromatin dynamics are epigenetically regulated and are required for stress-induced transcriptional regulation or reprogramming. Epigenetic regulators facilitate the phenotypic plasticity of developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 167 publications
0
41
0
Order By: Relevance
“…As an alternative hypothesis, Mazzoleni et al, 2015 [ 1 ] and later Cartenì et al, 2016 [ 7 ] suggested a different explanation based on a more direct effect, i.e., the possible “interference” of extracellular self- or “similar” DNA (e.g. : homologous, i.e., from phylogenetically related species or even similar, i.e., with convergent structure similarity, although not phylogenetically related) causing inhibition of the whole cell functionality, mediated by sequence-specific recognition of small-sized nucleotide molecules [ 99 ], which could hamper cell and gene expression functionality [ 100 ] or affect genome stability [ 101 ], inhibiting the growth. This could explain the self-DNA growth inhibition as a widely conserved property of living beings, and therefore justify its observation over a very wide range of organisms spanning from prokaryotes to metazoan [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative hypothesis, Mazzoleni et al, 2015 [ 1 ] and later Cartenì et al, 2016 [ 7 ] suggested a different explanation based on a more direct effect, i.e., the possible “interference” of extracellular self- or “similar” DNA (e.g. : homologous, i.e., from phylogenetically related species or even similar, i.e., with convergent structure similarity, although not phylogenetically related) causing inhibition of the whole cell functionality, mediated by sequence-specific recognition of small-sized nucleotide molecules [ 99 ], which could hamper cell and gene expression functionality [ 100 ] or affect genome stability [ 101 ], inhibiting the growth. This could explain the self-DNA growth inhibition as a widely conserved property of living beings, and therefore justify its observation over a very wide range of organisms spanning from prokaryotes to metazoan [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutant analyses revealed that this two-lysine-specific demethylase induces immune memory by activating WRKY transcription factors (WRKY 22/40/70) in Arabidopsis upon Pseudomonas syringae infection [ 54 ]. The complex interplay between DNA modifiers, regulating non-coding RNAs (ncRNA), chromatin remodelers and histone modifiers contributes phenotypic plasticity to sessile plants to perform better in the host–microbe interaction and the generation of stress memory [ 55 ]. Comparative proteomic analysis in Pinus sp .…”
Section: Epigenetic Regulation Of Plant Memorymentioning
confidence: 99%
“…“Memory” is usually defined for this long-term memory, which impregnate the marks in the genome in the form of acetylation, methylation, ubiquitination, SUMOylation, etc. [ 55 , 87 ]. Such situations can reprogram the transcriptional and translational machinery of the organism.…”
Section: Priming Vs Memory and The Fine Line Of The Differencementioning
confidence: 99%
“…In the natural environment, plants sense and respond to developmental and environmental cues by dedicated signaling pathways, which ultimately leads to extensive reprogramming of the transcriptome essential to various biological processes, including plant growth, development, and adaptation to environments [1,2]. Increasing evidence has revealed that plants have evolved sophisticated regulatory mechanisms to tightly control this transcriptomic reprogramming [1,2]. Transcription factors usually function as major regulators governing the expression of their target genes in response to developmental and environmental cues [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that plants have evolved sophisticated regulatory mechanisms to tightly control this transcriptomic reprogramming [1,2]. Transcription factors usually function as major regulators governing the expression of their target genes in response to developmental and environmental cues [1,2]. In addition, epigenetic processes and elements such as DNA methylation, histone post-translational modifications, chromatin remodeling, and noncoding RNAs (ncRNAs) are also widely involved in the regulation of gene expression at the transcriptional level, and play key roles in modulating plant developmental processes and responses to environmental stresses [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%